2022
DOI: 10.1038/s41431-022-01269-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous and homozygous variants in STX1A cause a neurodevelopmental disorder with or without epilepsy

Abstract: The neuronal SNARE complex drives synaptic vesicle exocytosis. Therefore, one of its core proteins syntaxin 1A (STX1A) has long been suspected to play a role in neurodevelopmental disorders. We assembled eight individuals harboring ultra rare variants in STX1A who present with a spectrum of intellectual disability, autism and epilepsy. Causative variants comprise a homozygous splice variant, three de novo missense variants and two inframe deletions of a single amino acid. We observed a phenotype mainly driven … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Table 2 shows that a parallel can be drawn between the culture experiments and gene dosage and pain sensitivity status in humans: 1 or 2 copies of the STX1A gene in individuals with WS (+/–) or their siblings (+/+), respectively, supports adequate nociceptive functions, whereas 3 copies are inhibitory. Although the effects of a full STX1A knockout in humans are currently unknown, it likely would involve other severe phenotypic presentations ( 31 ). However, extrapolating to include the Stx1a -knockout mouse, which exhibits an increased nociceptive phenotype ( 32 ), then nociceptive responsiveness ranges from enhanced sensitivity with 0 copies (mouse), to normal with 1 or 2 copies, and inhibited with 3 copies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows that a parallel can be drawn between the culture experiments and gene dosage and pain sensitivity status in humans: 1 or 2 copies of the STX1A gene in individuals with WS (+/–) or their siblings (+/+), respectively, supports adequate nociceptive functions, whereas 3 copies are inhibitory. Although the effects of a full STX1A knockout in humans are currently unknown, it likely would involve other severe phenotypic presentations ( 31 ). However, extrapolating to include the Stx1a -knockout mouse, which exhibits an increased nociceptive phenotype ( 32 ), then nociceptive responsiveness ranges from enhanced sensitivity with 0 copies (mouse), to normal with 1 or 2 copies, and inhibited with 3 copies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in genes mediating the synaptic docking process, including STX1A , are rare. Individuals harboring mutations in STX1A have not been carefully studied for alterations in pain sensitivity, though it is interesting to note that different phenotypes occur if the mutations involve interaction with STXBP1, which normally inhibits STX1A-SNARE interactions, or the domain of STX1A that interacts directly with the other 2 members of SNARE complex ( 31 ). This raises the possibility that the inhibitory effects of overexpression of STX1A protein may vary based on genetic variation in other interacting SNARE proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This structure consists of two SNAP25 helices (encoded by SNAP25), one syntaxin 1A helix (encoded by the STX1A gene), and one synaptobrevin 2 helix (encoded by VAMP2) [17]. Causative variants within these genes responsible for SNARE protein synthesis encompass a wide array of genetic alterations, including homozygous splice variants, de novo missense variants, and in-frame deletions affecting only a few amino acids [18].…”
Section: Of 12mentioning
confidence: 99%
“…Exome and genome sequencing remain critical to diagnosis of rare disease, and identification of novel genomic causes. In March 2023, Luppe et al reported mono-and bi-allelic variants in STX1A as causing a novel neurodevelopmental disorder [10]. Genome sequencing identified that copy number variants of FGF14 underlie a condition of early onset nystagmus and variable ataxia [11] while ARHGAP35 was identified as causing a range of anterior chamber malformations [12].…”
mentioning
confidence: 99%